2016
DOI: 10.1177/1553350616663322
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Acquisition of Complex Techniques

Abstract: Background Complex procedures often have numerous acceptable approaches; it is unclear how surgical fellows choose between techniques. We used pancreaticoduodenectomy as a model to catalogue variability between surgeons and investigate factors that affect fellows' acquisition of techniques. Materials and methods Semistructured interviews and operative note analysis were conducted to determine techniques of 5 attending surgeons, and these data were mapped to identify variations. Identical interviews and questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Asch et al 39 showed that imprinting of procedural variations and their associated complication rates may follow surgeons from their postgraduate training programs to their jobs in independent practice. And, most convincingly, Davidson et al 40 used the example of pancreaticoduodenectomy to demonstrate that although surgical procedures may in theory have relatively few variations, in practice they are significantly more complex. Davidson et al 40 closely examined the pancreaticoduodenectomy of 5 surgeons and found they differed in "steps and techniques employed" (p. 2) for 7 major areas of the procedure and 21 minor areas.…”
Section: Disagreement On Applying Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Asch et al 39 showed that imprinting of procedural variations and their associated complication rates may follow surgeons from their postgraduate training programs to their jobs in independent practice. And, most convincingly, Davidson et al 40 used the example of pancreaticoduodenectomy to demonstrate that although surgical procedures may in theory have relatively few variations, in practice they are significantly more complex. Davidson et al 40 closely examined the pancreaticoduodenectomy of 5 surgeons and found they differed in "steps and techniques employed" (p. 2) for 7 major areas of the procedure and 21 minor areas.…”
Section: Disagreement On Applying Principlesmentioning
confidence: 99%
“…And, most convincingly, Davidson et al 40 used the example of pancreaticoduodenectomy to demonstrate that although surgical procedures may in theory have relatively few variations, in practice they are significantly more complex. Davidson et al 40 closely examined the pancreaticoduodenectomy of 5 surgeons and found they differed in "steps and techniques employed" (p. 2) for 7 major areas of the procedure and 21 minor areas. They concluded that each of the 5 surgeons in the study essentially performed 5 different procedures but "all called (it) a Whipple's procedure" (p. 2) .…”
Section: Disagreement On Applying Principlesmentioning
confidence: 99%
See 1 more Smart Citation